Diseño de un plan de mantenimiento para las máquinas de generación de la central hidroeléctrica Illuchi - Hidalgo Negrete, Joel Aldemar (2018)
This resaerch Project began with a colletion of maintenace information performed at the hidroelectric power station then each of their systems were identified, these are: driving, generation, excitation system, lubrication, cooling, control system and measure systems, after that, the plans were made with each equipment and elements. Besides a theoretical compilation of maintenance based on RCM reliability with information to complete the RCM worksheet and the RCM decision worksheet. Subsequently, a mode analysis, the mode, cause and effect of failure was made and assume that it has on the RCM worksheet. By calculation, availability and reliability was obtained, having as one 95% of the four units, because they are related. The maintenance plan was designed with Microsoft Excel program, because in these plants work with system, the frequencies of this plan are with the hours of operation of each units, but for different reasons the units don't work twenty four continuous hours and allowed maintenance in real time, this plan consist of four alarms: green, yellow, orange and red which are activated in the mentioned order according to the working hours.